INOVASI EDUKASI: AUGMENTED REALITY UNTUK TATALAKSANA JENAZAH DALAM KONTEKS ISLAM - Resiasa, Maskuri; Unik, Mitra (Department of Information System Muhammadiyah University of Riau, 2024)
This research successfully addresses the complexity of handling corpses within an Islamic framework through the application of educational innovations using Augmented reality (AR) technology. The AR Jenazah application was developed with a focus on increasing understanding and skills in corpse handling procedures, which are in accordance with religious teachings and ethical norms. The results of black box testing showed the reliability of the application's functionality and presentation, while beta testing with the participation of 20 general public respondents gave positive conclusions on user interest, teaching, ease of use, and application performance. This research makes an important contribution to the development of a modern educational approach in understanding and implementing corpse handling procedures in an Islamic context. The AR Jenazah application was not only technically successful, but also achieved positive user acceptance, signalling its potential positive influence in improving the quality of learning and practice of corpse handling. Suggestions for development involve expansion of educational content, expert and user engagement, adoption to other platforms, evaluation of long-term impact, development of interactive features, multi-language versions, and collaboration with educational and religious institutions. These improvements are expected to strengthen the educational value of the app and expand its positive impact in the wider community.